2016
DOI: 10.1021/acs.est.6b03165
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights on the Photosensitized Chemistry of a Fatty Acid at the Air/Water Interface

Abstract: Interfaces are ubiquitous in the environment and many atmospheric key processes, such as gas deposition, aerosol, and cloud formation are, at one stage or another, strongly impacted by physical and chemical processes occurring at interfaces. Here, the photoinduced chemistry of an air/water interface coated with nonanoic acid—a fatty acid surfactant we use as a proxy for chemically complex natural aqueous surface microlayers—was investigated as a source of volatile and semivolatile reactive organic species. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
132
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(143 citation statements)
references
References 48 publications
9
132
2
Order By: Relevance
“…[2][3][4][5]40 In agreement, the same VOC classes were observed for the biofilm samples investigated in this work (Table 1 and Supplementary Information). In particular, not only saturated 15 oxygenated VOCs, such as aldehydes and ketones, but also unsaturated and functionalized VOCs were observed (e.g., alkenes, dienes, unsaturated aldehydes or ketones).…”
Section: Resultssupporting
confidence: 84%
See 4 more Smart Citations
“…[2][3][4][5]40 In agreement, the same VOC classes were observed for the biofilm samples investigated in this work (Table 1 and Supplementary Information). In particular, not only saturated 15 oxygenated VOCs, such as aldehydes and ketones, but also unsaturated and functionalized VOCs were observed (e.g., alkenes, dienes, unsaturated aldehydes or ketones).…”
Section: Resultssupporting
confidence: 84%
“…In the past, it was shown that unique photochemical reactions with significant implications for atmospheric processes can occur at such interfaces, leading to the formation of volatile organic 5 compounds (VOCs) [1][2][3][4][5] and secondary organic aerosols, 6 or acting as sinks for reactive species, such as NO 2 or ozone. [7][8][9][10] This interfacial photochemistry is exclusively due to the presence of surfactants which tend to concentrate in surface layers with respect to the underlying bulk water.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations